Radiological Assessment of Building Materials Containing Processed Bauxite - Uku Andreas Reigo; Cansu Özcan Kılcan; Alan H. Tkaczyk (Journal of Nuclear Engineering, 2025)
Supplementary cementitious materials (SCMs) may be prepared using industrial byproduct streams, aiding in the development of a more environmentally sustainable circular economy. However, these byproducts may carry a risk of exhibiting elevated levels of radioactivity because of the preceding processing that may have concentrated the radionuclides naturally occurring in the raw material. This processing causes the byproducts to be considered technologically enhanced naturally occurring radioactive material (NORM). Thus, the safe use of such SCMs requires robust data on the activity concentrations of three main radionuclides (226Ra, 232Th, 40K) represented by the activity concentration index (ACI) used as a radiological suitability indicator. In this work, candidate SCMs derived from the alumina industry byproduct processed bauxite (PB), also referred to as bauxite residue, were assessed by measuring the activity of all available samples, including input raw materials and intermediate substances, through gamma spectrometry. PB was found to significantly impact the final ACI value of the building material. As a key analysis outcome applicable to the substances assessed in this work, no additional dose assessment is required, given the low ACI value of the building materials. This result indicates that, from a radiological perspective, the PB samples studied are suitable precursors for SCMs. In addition, a generalized approach was found to provide good estimations of the ACI value of building materials, which is useful to screen materials for regulatory compliance, without needing to prepare samples of the materials in question.